Bromodomain-containing Protein 4 Activates Voltage-gated Sodium Channel 1.7 Transcription in Dorsal Root Ganglia Neurons to Mediate Thermal Hyperalgesia in Rats. (November 2017) - Hsieh, Ming-Chun; Ho, Yu-Cheng; Lai, Cheng-Yuan; Wang, Hsueh-Hsiao; Lee, An-Sheng; Cheng, Jen-Kun; Chau, Yat-Pang; Peng, Hsien-Yu
Abstract : Background: Bromodomain-containing protein 4 binds acetylated promoter histones and promotes transcription; however, the role of bromodomain-containing protein 4 in inflammatory hyperalgesia remains unclear. Methods: Male Sprague–Dawley rats received hind paw injections of complete Freund's adjuvant to induce hyperalgesia. The dorsal root ganglia were examined to detect changes in bromodomain-containing protein 4 expression and the activation of genes involved in the expression of voltage-gated sodium channel 1.7, which is a key pain-related ion channel. Results: The intraplantar complete Freund's adjuvant injections resulted in thermal hyperalgesia (4.0 ± 1.5 s; n = 7). The immunohistochemistry and immunoblotting results demonstrated an increase in the bromodomain-containing protein 4–expressing dorsal root ganglia neurons (3.78 ± 0.38 fold; n = 7) and bromodomain-containing protein 4 protein levels (2.62 ± 0.39 fold; n = 6). After the complete Freund's adjuvant injection, histone H3 protein acetylation was enhanced in the voltage-gated sodium channel 1.7 promoter, and cyclin-dependent kinase 9 and phosphorylation of RNA polymerase II were recruited to this area. Furthermore, the voltage-gated sodium channel 1.7–mediated currents were enhanced in neurons of the complete Freund's adjuvant rats (55 ± 11 vs. 19 ± 9 pA/pF; n = 4 to 6 neurons). Using bromodomain-containing protein 4–targeted antisense small interfering RNA to the complete Freund's adjuvant–treated rats, the authors demonstrated a reduction in the expression of bromodomain-containing protein 4 (0.68 ± 0.16 fold; n = 7), a reduction in thermal hyperalgesia (7.5 ± 1.5 s; n = 7), and a reduction in the increased voltage-gated sodium channel 1.7 currents (21 ± 4 pA/pF; n = 4 to 6 neurons). Conclusions: Complete Freund's adjuvant triggers enhanced bromodomain-containing protein 4 expression, ultimately leading to the enhanced excitability of nociceptive neurons and thermal hyperalgesia. This effect is likely mediated by the enhanced expression of voltage-gated sodium channel 1.7. Abstract : Using a rat model of inflammatory pain, it was observed that bromodomain-containing protein 4 expression was increased in dorsal root ganglia. Higher levels of bromodomain-containing protein 4 were associated with the increased expression of voltage-gated sodium channel 1.7, larger transmembrane sodium currents, and more profound hyperalgesia.Supplemental Digital Content is available in the text.